Makna Upacara Adat Panggih Pernikahan Adat Jawa di CV Aksara Multikreasi Menurut Perspektif Hukum Urf dalam Khasanah Islam - Oktaviana, Gesy Lutfiah Rosidah; Werdiningsih, Yuli Kurniati; Sunarya, Sunarya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
In general, this research was conducted to find out clearly the intended meaning of a series of traditional Panggih processions at weddings that use Javanese customs and traditions. This research, which is based on issues related to the harmony of religious and cultural values ​​towards a tradition, chooses to focus the discussion on the legal perspective of urf in Islamic rules. The researcher aims to find out how the Islamic religion views the panggih procession at traditional Javanese weddings when it is linked to cultural aspects and norms that apply in society. This research focuses on collecting and interpreting qualitative data obtained from clients who use wedding organizer services, namely CV Aksara Multikreasi. In compiling it, the author used a collection of data from direct observations of CV Aksara Multikreasi clients who were involved and who carried out Javanese traditional wedding processions to then be analyzed inductively. Based on this, the research results show that the meaning contained in the panggih procession in the form of balangan gantal, ngidak tigan, and wijikan in traditional Javanese ceremonies is in line with the breath and rules of Islam from the perspective of urf law. Therefore, with this research, it is hoped that it will be able to become a source of information for the community regarding the law of implementing traditions or customs that are customary in certain communities from a religious perspective, so that in the development of science and technology there will be no conflict of arguments regarding the validity of religious and cultural values.